ORGANIZATIONAL EFFECTIVENESS IN IMPLEMENTATION OF DYNAMIC ARCHIVES INFORMATION SYSTEMS (SIKD) AT THE DEPARTMENT OF BANDUNG CITY LIBRARY AND ARCHIVES - Soma Gantika; Hari Busthomi; Regan Vaughan (JEES: Journal of Economic Empowerment Strategy, 2022)
Dynamic Archive Information System (SIKD) is one of the supports so that archives can be neatly organized, makes it easy for employees to input dynamic archives, and is easy to browse because data and documents are stored electronically. This study aims to describe and analyze the extent to which the Organizational Effectiveness in the Implementation of Dynamic Archival Information Systems in the Office of Libraries and Archives of Bandung City. In the report on the results of this research will be discussed about the effectiveness of the organization in the implementation of the Dynamic Archives Information System, the obstacles faced and the efforts made by the Department of Library and Archives of Bandung City. This research uses qualitative research methods. The data collection techniques used were observation, interviews and documentation. In this study, the benchmark for Organizational Effectiveness is the theory of Richard M. Steers (1985), namely Organizational Characteristics, Environmental Characteristics, Worker Characteristics, and Management Policies / Practices. The parties who became informants in this study were the Head of Archives Management, the Head of the Archive Publication and Preservation Section, the Head of the Dynamic Archives Management Section, Associate Expert Archivist, and the First Archivist. This research shows that the effectiveness of the organization in implementing the Dynamic Archival Information System has been carried out but has not been maximized, this is due to the lack of training and development of employees regarding Dynamic Archival Information Systems, lack of internet facilities so that they often experience disruption.